(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The practice of social work is constantly confronted with the need of helping people in difficult life circumstances. The formal criterion of material security appears to be clearly insufficient for the development of programs to support and develop people in a critical life situation. Dynamic changes in the objective conditions of people’s life can differently affect the structure and content of life activity, which depends on the degree of directness or indirectness of their subjective values for the organization and implementation of individual activities. The degree of influence of objective changes is experienced by the individual as a degree of personal difficulties, rallied to a personal crisis and a life catastrophe. Complex life circumstances are manifested in the deprivation of opportunities for self-provision of life needs and self-realization of the individual. They are experienced by the individual as an opportunity to live under such conditions while experiencing the possibility of changing the conditions of life. The change in the objective circumstances of life should be understood by the individual as a task for self-change, which ensures the development of new programs of activity adequate to the changes that have occurred. The lack of such readiness for self-change is the main barter on the path to successful adaptation or re-adaptation of a person in changing living conditions. Such understanding of the psychological structure of difficult life circumstances allows the development and implementation of new, more effective technologies of social work with people in crisis conditions.